Oligomeric ricinoleic acid synthesis with a recyclable catalyst and application to preparing non-isocyanate polyhydroxyurethane. (15th June 2021) - Ren, Fang-Yu; You, Fei; Gao, Song; Xie, Wei-Hang; He, Liang-Nian; Li, Hong-Ru
Graphical abstract: Highlights: A series of ricinoleic acid based non-isocyanate polyurethanes were fabricated. Oligomeric ricinoleic acid (ORA) was designed as the key intermediate. SnO was developed as an efficient and recyclable catalyst to access the ORA. The polymerization degree of ORA can be regulated by reaction time. The properties of polyurethanes can be altered by the polymerization degree of ORA. Abstract: As a consequence of the great demand and extended application of polyurethanes in various fields, the development of green processes for their production and functional polyurethane materials has received widespread attention. In this regard, the biomass-derived polyurethane via the non-isocyanate route could be promising. In this work, the castor-based polyurethanes were designed and synthesized through a non-isocyanate route by employing ricinoleic acid as the starting material, in which the oligomeric ricinoleic acid (ORA) with variable average polymerization degree was used as the key intermediate. To access the ORA with different average polymerization degree, the solid Lewis acid tin(II) oxide (SnO) was developed as the efficient and recyclable catalyst and the average polymerization degree of ORA was regulated by the reaction time at 210 °C. After sequential esterification, epoxidation, cycloaddition with CO2 and polyaddition with 1, 6-hexamethylene diamine (HMDA) or isophorone diamine (IPDA), a series of polyhydroxyurethanes (PHUs) with different tensile strength and elongation at break as well as the thermal stability and the glass transition temperature were obtained depending on the type of diamine and the average polymerization degree of ORA, indicating the functional role of the polymerization degree of ORA in regulating the mechanical and thermal properties of the resulting materials. This protocol for the castor-based PHUs preparation in this work not only represents a green and sustainable way to produce bio-based material, but also provides a convenient way to change the average polymerization degree of ORA and then alter the properties of resulting polyurethanes.